The Influence of Communication, Self Esteem and Self Efficacy on Nurse Performance at H. Abdul Manan Simatupang Kisaran General Hospital - Faulia Anggeraini; Hajar Affiah (International Journal of Economics (IJEC), 2023)
This study aims to determine the simultaneous and partial effect of Communication, Self Esteem and Self Efficacy on Performance. The number of samples is 50 respondents. The F-test produces a value of Fcount (26.524) > Ftable (2.81), meaning that simultaneously communication, self-esteem, self-efficacy have a significant effect on improving nurse performance. The results of the t-test, partially tcount (8.818) > ttable (2.01174) and significance value (0.023 <0.05) means that communication has a positive and significant effect on performance. The tcount (2.445) > ttable (2.01174) and the significance value (0.021 <0.05) means that partially self-esteem has a positive and significant effect on performance. The tcount value (2.346) > ttable (2.01174) and the significance value (0.017 <0.05) means that partially self-efficacy has a positive and significant effect on performance. The R2-test produces a coefficient of determination equal to communication, self-esteem and self-efficacy is able to explain the performance of 61%, while the remaining 39% is explained by other variables not included in this study.